2021
DOI: 10.1071/an20248
|View full text |Cite
|
Sign up to set email alerts
|

Substantial genetic gains in reducing breech flystrike and in improving productivity traits are achievable in Merino sheep by using index selection

Abstract: Context. The availability of effective indirect rather than direct selection criteria for genetically reducing breech flystrike is crucial for the Australian wool industry, as expression of breech flystrike is routinely suppressed by management interventions to minimise the risks to sheep health, welfare and productivity. Understanding how much genetic gain can be made in reducing breech strike, while also selecting for other key traits is important in choosing breeding objectives, particularly for Merino gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Breeding for resistance to parasites has long been recognised as the most effective long-term solution for those parasitic diseases of livestock for which significant levels of heritable resistance to infection have been identified. The potential for breeding to provide resistance to infection has been described for the cattle tick, 64,65 the sheep blowfly, [66][67][68] intestinal worms of sheep [69][70][71] goats 72 and cattle, 73 sheep louse, 74 sheep liver fluke, 75 and buffalo fly. 76 However, there are a number of issues that act against the widespread adoption of breeding for parasite resistance in livestock, including the slow rate of progress in increasing resistance within a flock/herd, the lack of direct phenotypic measures of resistance in some cases (e.g.…”
Section: Breedingmentioning
confidence: 99%
“…Breeding for resistance to parasites has long been recognised as the most effective long-term solution for those parasitic diseases of livestock for which significant levels of heritable resistance to infection have been identified. The potential for breeding to provide resistance to infection has been described for the cattle tick, 64,65 the sheep blowfly, [66][67][68] intestinal worms of sheep [69][70][71] goats 72 and cattle, 73 sheep louse, 74 sheep liver fluke, 75 and buffalo fly. 76 However, there are a number of issues that act against the widespread adoption of breeding for parasite resistance in livestock, including the slow rate of progress in increasing resistance within a flock/herd, the lack of direct phenotypic measures of resistance in some cases (e.g.…”
Section: Breedingmentioning
confidence: 99%
“…Brien et al 147 extended these studies by including all three of the main indirect criteria for which ASBVs are available in MERINOSELECT (breech wrinkle, dag and breech cover) and examined the rates of gain in flystrike resistance that could be made by adding flystrike as a trait to three MERINOSELECT indices: Dual Purpose Plus (DP+), Fibre Production Plus (FP+) and the Merino Production Plus (MP+). They showed that substantial genetic gains in flystrike resistance could be made without unrealistically compromising rates of genetic improvement in the other production traits.…”
Section: Breedingmentioning
confidence: 99%
“…In the long-term, painful procedures are not socially sustainable, as public concern for farm animal welfare continues to grow (Fernandes et al, 2021). Ultimately, the goal is to phase out painful procedures through the development of improved housing, management, and breeding practices (e.g., Knierim et al, 2015;Scheper et al, 2016;Nicol, 2018;Yunes et al, 2019;Brien et al, 2021;Gascoigne et al, 2021). In the shortterm, continued research on strategies to refine current practices is needed, including greater analgesic coverage, modifications to the rearing environment such as increasing maternal and social contact and nutritional allowances, and performing the procedure with the most appropriate method and at an age that is least detrimental to short-and long-term welfare.…”
Section: Welfare Implicationsmentioning
confidence: 99%